Voices of change: Principal stakeholder experiences in a participatory approach to educational transitions - Irati Sagardia-Iturria; Agurtzane Martinez-Gorrotxategi; Alexander Barandiaran-Arteaga (Educar, 2025)
The experiences and participation of all individuals involved in educational transitions are key to fully understanding the factors that facilitate or hinder these processes. Furthermore, these experiences can serve as a driving force for the continuous improvement of transition processes and related aspects at both the school and community levels. The aim of this research is to understand and transform educational transition processes using a participatory action research method. The study was conducted in a primary and secondary school in Gipuzkoa over three academic years, involving all children participating in educational transitions, as well as their families and teachers. Data were collected through questionnaires for families, semi-structured interviews with teachers, and participatory techniques to engage the children. The findings from the second research cycle revealed that the design of an action plan to improve transitions created new structures for teacher coordination and led to changes in school culture, emphasising the importance of listening to children and their families when designing improvement actions.